Isnad Al-hadith computational authentication: An analysis hierarchically - Ibrahim, Nuzulha Khilwani; Noordin, Mohamad Fauzan; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Ahmed Ali, Ahmed El-Mogtaba Bannga (The Institute of Electrical and Electronics Engineers, Inc., 2016)
According to muhaddithun, hadith is ‘what was transmitted on the authority of The Prophet (PBUH): his deeds, sayings, tacit approvals, or description of his physical features and moral behaviors’. These days, there are an increasing number of studies in Information Technology (IT) has been done on hadith domain in different levels of knowledge of hadith, where a number of studies have been conducted in IT to validate the hadith where most of them are based on the matching of test hadith with the authentic Ahadith in the database. However, there are limited computerizedbased studies to authenticate the hadith based on scholars’ principles. This paper discusses an analysis to produce a hierarchy with different levels of related studies in computational hadith to link with the computational authentication of isnad al-hadith science. The result from the analysis is the deepest level of hadith authentication where we presented the existing studies conducting hadith authentication based on principles of hadith authentication in hadith science. While the future work of the analysis is a computational authentication of isnad al-hadith based on commonly agreed principles in hadith.